Personality and interpersonal value correlates of academic over- and under-achievement - Navarez, Maria Garfin 1942-
Scientific personality assessment has its roots in the study of individual differences through psychological measurement. This study tried to determine and describe the personality traits and interpersonal values of a group of sophomores and seniors of the Marcial O. Rañola Memorial School, S.Y. 1978-1979. Some of the instruments used in the study were the Culture Fair Test of "g" Scale 2 Form A and Cattell's High School Personality Questionnaire (HSPQ). Conclusion drawn from the study showed that intelligence, excitability, superego strength, thick-skinned venturesomeness, protected emotional sensitivity, self-sufficiency and will-power contributed significantly to the academic performance of the over- and underachievers involved in this study.